To be or not to be : understanding entrepreneurial and professional motivations of undergraduates in Singapore - Hong, Amy Yee Cheng (2011)
This study utilised a personality trait and values approach to explain the polarity between Entrepreneurial Intention (EI) and Professional Intention (PI) found by Chan et al (2011), by using Entrepreneurial Motivation (EM) and Professional Motivation (PM) as intermediate constructs. Personality trait and value factors under investigation include risk aversion, uncertainty avoidance and Schwartz’s universal human values. Through correlation and regression analyses, risk aversion was found to be a predictor of EM, while uncertainty avoidance was found to be a predictor of PM. The relationship between Schwartz’s universal human values with EM and PM were not fully supported. Implications and suggestions for future research were discussed.